2022
DOI: 10.1186/s12870-022-03521-z
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide characterization and expression analysis of Erf gene family in cotton

Abstract: Background AP2/ERF transcription factors are important in a variety of biological activities, including plant growth, development, and responses to biotic and abiotic stressors. However, little study has been done on cotton’s AP2/ERF genes, although cotton is an essential fibre crop. We were able to examine the tissue and expression patterns of AP2/ERF genes in cotton on a genome-wide basis because of the recently published whole genome sequence of cotton. Genome-wide analysis of ERF gene famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 81 publications
3
37
0
Order By: Relevance
“…The similarity in gene structure and distribution of conserved motifs in the same subclade suggested that they had similar roles in plant growth ( Zafar et al., 2022 ). The distribution of motifs varied among different subclades.…”
Section: Discussionmentioning
confidence: 99%
“…The similarity in gene structure and distribution of conserved motifs in the same subclade suggested that they had similar roles in plant growth ( Zafar et al., 2022 ). The distribution of motifs varied among different subclades.…”
Section: Discussionmentioning
confidence: 99%
“…The phylogenetic trees of DREB subfamily genes from four cottons were constructed by MEGA (V7.0) software. The multiple sequence alignment of protein sequences for DREB genes coding region in Arabidopsis and four cottons ( G. barbadense , G. hirsutum , G. arboreum , and G. raimondii ) were carried out by ClustalW tool with default parameters [ 55 ]. The best model of phylogenetic tree was calculated and constructed with MEGA, and then a phylogenetic tree of all DREB proteins was constructed using the maximum likelihood method with the following parameters: poisson correction, pairwise deletion, and 1000 bootstrap replicate.…”
Section: Methodsmentioning
confidence: 99%
“…Synteny analysis can identify chromosome structural changes and homologous gene evolutionary and functional connections in multiple genomes [ 50 , 51 ]. In this study, synteny analysis showed that the collinear gene pairs of E. fulvus and sorghum were densely distributed on chromosomes and had one-to-one correspondence, indicating that the genes E. fulvus and sorghum were homologous, and both of these species may have emerged in the same period of evolution ( Figure 7 ).…”
Section: Discussionmentioning
confidence: 99%